Rancang Bangun Aplikasi Penerimaan Siswa Baru di SMA Gerardus Mayella Kalembu Weri - Petrus Maghu Ate; Gergorius Kopong Pati; Karolus Wulla Rato (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
Gerardus Mayella Kalembu Weri High School is a school that operates in the field of educational institutions which currently still has problems with the process of admitting new students requiring quite a long time in filling out paper forms and student data still using the main book as a medium for storing student data. Then the committee will input or copy student data on the computer, which is a problem regarding new student registration which is still manual, which of course keeps the committee busy in terms of new student registration. And the data could be lost because it is still in the form of sheets of paper. System This can be more efficient in terms of costs, energy and time, so that it is effective in achieving goals. In accessing the current system, we sometimes experience obstacles in implementing information, such as accepting new students. For this reason, a special information system is needed to overcome this problem, namely an online registration information system. This system was developed using web engineering methods. The method is used to create a web-based application system using engineering science, management principles and a systematic approach so that high quality web systems and applications can be obtained.